Phenotypic and functional heterogeneity of bovine blood monocytes. - Jamal Hussen; Anna Düvel; Olivier Sandra; David Smith; Iain Martin Sheldon; Peter Zieger; Hans-Joachim Schuberth (PLoS ONE)
Murine and human peripheral blood monocytes are heterogeneous in size, granularity, nuclear morphology, phenotype and function. Whether and how bovine blood monocytes follow this pattern was analyzed in this study. Flow cytometrically, classical monocytes (cM) CD14⁺CD16⁻, intermediate monocytes (intM) CD14⁺ CD16⁺ and nonclassical monocytes (ncM) CD14⁺ CD16⁺ were identified, with cM being the predominant subset (89%). cM showed a significant lower expression of CD172a, intM expressed the highest level of MHC class II molecules, and ncM were low positive for CD163. Compared to cM and intM, ncM showed a significantly reduced phagocytosis capacity, a significantly reduced generation of reactive oxygen species, and reduced mRNA expression of CXCL8, CXCL1 and IL-1β after LPS stimulation. Based on IL-1β secretion after LPS/ATP stimulation, the inflammasome could be activated in cM and intM, but not in ncM. IFNγ increased the expression of CD16 selectively on cM and induced a shift from cM into intM in vitro. In summary, bovine CD172a-positive mononuclear cells define three monocyte subsets with distinct phenotypic and functional differences. Bovine cM and intM share homologies with their human counterparts, whereas bovine ncM are not inflammatory monocytes.